Theoretical illumination of highly original photoreactive 3MC states and the mechanism of the photochemistry of Ru(ii) tris(bidentate) complexes. Issue 40 (9th October 2017) - Dixon, Isabelle M.; Heully, Jean-Louis; Alary, Fabienne; Elliott, Paul I. P.
Abstract : Elucidation of the photoreactive mechanism of ruthenium(ii ) complexes is reported along with identification of crucial and highly original metal-centred states. Abstract : We have identified highly novel photoreactive 3 MC states of ruthenium(ii ) 4, 4′-bi-1, 2, 3-triazolyl (btz) complexes of the form [Ru(N^N)(btz)2 ] 2+ and have elucidated the mechanism of the highly unusual experimental observations of photochemical ligand dechelation and concomitant ligand rearrangement reactivity to form unusual photoproducts trans -[Ru(N^N)(κ 2 -btz)(κ 1 -btz)(solvent)] 2+ . The triplet metal-to-ligand charge-transfer ( 3 MLCT) states and classical Jahn–Teller type triplet metal-centred ( 3 MC) states of the series of complexes [Ru(N^N)3− n (btz) n ] 2+ (btz = 4, 4′-bi-1, 2, 3-triazolyl; N^N = 2, 2′-bipyridyl (bpy), n = 0 (1 ), 1 (2 ), 2 (3 ), 3 (5 ); N^N = 4-(pyrid-2-yl)-1, 2, 3-triazole (pytz), n = 1 (4 )) have been optimised by density functional theory (DFT) and characterised. There is a gradual and significant destabilisation of the 3 MLCT states as the triazole content of the complexes increases, which occurs with a slight stabilisation of the 3 MC states. Whilst consistent with the promotion of photochemical reactivity in the heteroleptic complexes of the series relative to1, these classical 3 MC states fail to account for the extraordinary ligand rearrangement processes that accompany ligand ejection. Thorough theoretical exploration of the lowest excited triplet potential energy surface ( 3 PES) here reveals the existence of a new type of 3 MC state and the role it plays in the photochemical reactivity of the complexes. This newly discovered state, called MC(F), displays a flattened geometry (indicated by the 'F' in the parentheses) which makes it clearly on the path to achieving the coplanarity of the bidentate ligands in the experimentally observed trans -photoproduct. Further novel 'pentacoordinate' 3 MC states with coplanar bidentate ligands, called MC(P) (where the 'P' in the parentheses denotes the pentacoordinate character), were then identified and optimised. The energy barriers between the different triplet states were confirmed to be small which makes all triplet states accessible. Solvent trapping, which occurs on the singlet PES according to Wigner's rules, is finally achieved by a singlet pentacoordinate species to yield the monosolvento photoproduct. Thus, our calculations not only reveal highly novel 3 MC states but more significantly demonstrate their crucial role in the formation of the experimentally observed photoproducts.